Effects of Road Transportation on Some Physiological Stress Measures in Anpera and Boerka Goats - Gresy Eva Tresia; Arie Febre Trisiana; Bess Tiesnamurti (Buletin Peternakan, 2023)
Transporting livestock is a common practice in agriculture, but it can be a stressful situation for the animals. This stress can lead to physiological responses like live weight loss, changes in blood cortisol levels, and immune suppression. Goats are particularly sensitive to transportation stress and stress-induced diseases. In this study, we investigated the effects of road transport on the physiological condition of 33 goats (13 Anpera goats and 20 Boerka goats) transported for 72 hours over approximately ±2.000 km. Live weight loss was determined by comparing the body weights of the goats before and after transportation. We measured psychological responses (heart rate, respiratory rate, rectal temperature), blood parameters (Blood urea nitrogen/BUN, creatinine, glucose), cortisol, and hematological parameters. The results showed that transportation caused an average weight loss of 4.05 kg/head (14.22%). Heart rate decreased by 14.71 x/minute after transport, while respiratory rate and rectal temperature increased by 8.44 x/minute and 0.41 units, respectively. BUN levels increased by approximately 10.92 mg/dL (35%) and glucose levels increased by approximately 30.07 mg/dL (48%). Hematological parameters also showed significant changes, with transportation causing alterations in WBC, RBC, hemoglobin, hematocrit, MCV, and MCH levels. The study also showed an interaction between the sex and breed of goats on BUN, glucose, MCV, MCH. The comparison between Anpera goats and Boerka showed that transportation had significant influence on heart rate, rectal temperature, cortisol, RBC, haemoglobin, RDW. In conclusion, transportation for 72 hours caused stress on goats, leading to weight loss, changes in psychological behavior, and blood parameters, and the breed and sex of the goats played a crucial role in the observed changes.